INTERPRETASI LAPISAN BAWAH PERMUKAAN DI AREA PANAS BUMI GUNUNG TELOMOYO, KABUPATEN SEMARANG MENGGUNAKAN METODE GEOLISTRIK RESISTIVITY KONFIGURASI SCHLUMBERGER - Elida Septiana Putriutami; Udi Harmoko; Sugeng Widada (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
Geoelectric measurements and interpretation have been conducted to obtain subsurface structure information in Geothermal area of Telomoyo Mountain at Semarang regency using Schlumberger configurationWe obtain a potential difference and current from field data acquisition that can be used to calculate the apparent resistivity value. Then, the apparent resistivity value is processed using IPI2win program to determine the value of resistivity in each layer using geological information as validation. The geoelectric results showed the presence of fault structures such as normal faults down and the layers which has resistivity values at 116 Wm with a depth at 106 - 120 m from the surface of geoelectric line are interpreted as the upper boundaries of the Caprock layer. Keywords: Resistivity, Schlumberger, Geothermal, Telomoyo Mountain